Major infectious diseases of alpacas: I. Vírusok - Prágai, Andrea; Kovács, Alfréd (Animal welfare, Ethology and Housing Systems (AWETH), 2012)
Alpaca (Vicugna pacos) is a domesticated species of South American camelid. Native americans keep them because of fine wool. Many people breed alpacas all round in the world. In Hungary also can be find some breeders too, and number of the farms is growing up. Fortunately, alpacas generally quite hardy animals, rarely have health concerns. But it is important to know about some of the more common and more dangerous alpaca diseases just in case. It is major to really know each of your alpacas individually. When you are around your alpacas frequently, you will notice when one behaves slightly abnormally. By the time that you figure out that an alpaca is sick, it need to be a medical emergency.